Anxious Children and Adolescents Non‐responding to CBT: Clinical Predictors and Families' Experiences of Therapy. (30th October 2015) - Lundkvist‐Houndoumadi, Irene; Thastum, Mikael
Abstract : The purpose of the study was to examine clinical predictors of non‐response to manualized cognitive behaviour therapy (CBT) among youths (children and adolescents) with anxiety disorders, and to explore families' perspective on therapy, using a mixed methods approach. Non‐response to manualized group CBT was determined among 106 youths of Danish ethnicity (7–17 years old) with a primary anxiety disorder, identified with the Clinical Global Impression of Improvement Scale at the 3‐month follow‐up. Twenty‐four youths (22.6 %) had not responded to treatment, and a logistic regression analysis revealed that youths with a primary diagnosis of social phobia were seven times more likely not to respond, whereas youths with a comorbid mood disorder were almost four times more likely. Families of non‐responding youths with primary social phobia and/or a comorbid mood disorder ( n  = 15) were interviewed, and data were analysed through interpretative phenomenological analysis. Two superordinate themes emerged: youths were not involved in therapy work, and manualized group format posed challenges to families . The mixed methods approach provided new perspectives on the difficulties that may be encountered by families of non‐responding youths with a primary social phobia diagnosis and youths with a comorbid mood disorder during manualized group CBT. Clinical implications related to youths' clinical characteristics, and families' experience and suggestions are drawn. Copyright © 2015 John Wiley & Sons, Ltd. Key Practitioner Messages: Youths with an anxiety disorder, who had a primary social phobia diagnosis and those, who had a comorbid mood disorder, were more likely not to respond to manualized group CBT. Parents of those non‐responding youths often considered them as motivated to overcome their difficulties, but due to their symptomatology, they were unreceptive, reluctant and ambivalent and therefore not actively involved in therapy. The non‐responding youths with social phobia felt evaluated and nervous of what others thought of them in the group. The parents of the non‐responding youths with a comorbid mood disorder felt the group format placed restraints on therapists' ability to focus on their individual needs.